2022
DOI: 10.1371/journal.pone.0271492
|View full text |Cite
|
Sign up to set email alerts
|

Proteome and morphological analysis show unexpected differences between promastigotes of Leishmania amazonensis PH8 and LV79 strains

Abstract: Background Leishmaniases are diseases caused by Leishmania protozoans that affect around 12 million people. Leishmania promastigotes are transmitted to vertebrates by female phlebotomine flies during their blood meal. Parasites attach to phagocytic cells, are phagocytosed and differentiate into amastigotes. We previously showed that PH8 and LV79 strains of Leishmania amazonensis have different virulence in mice and that their amastigotes differ in their proteomes. In this work, we compare promastigotes’ infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…We have already shown that PH8 early stationary phase promastigotes bind more and are more efficiently phagocytized by murine macrophages after 5 min of contact compared to LV79 [ 35 ]. This short initial interaction between the host cell and Leishmania promastigotes is very important and may favor either intracellular survival or parasite elimination depending on the molecules involved [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have already shown that PH8 early stationary phase promastigotes bind more and are more efficiently phagocytized by murine macrophages after 5 min of contact compared to LV79 [ 35 ]. This short initial interaction between the host cell and Leishmania promastigotes is very important and may favor either intracellular survival or parasite elimination depending on the molecules involved [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…To analyze if the higher phagocytosis of PH8 promastigotes by macrophages leads to a higher infection rate after a longer period, we analyzed macrophage infection and parasite loads after 24 h. Infections were performed with promastigotes collected at day 4 and 6 of culture, corresponding to early stationary and late stationary phases, as reported [ 35 ]. Figure 1 shows infection levels from a representative experiment, indicating that PH8 infects a higher percentage of macrophages and leads to higher parasite loads.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations